The impact of Sexual Assault Nurse Examiner (SANE) program services on law enforcement investigational practices: a mediational analysis - Campbell, Rebecca Moira (Criminal justice and behavior, 2012)
Sexual assault nurse examiner (SANE) programs can be a vital resource to victims and the legal community. This study examined how police may use SANE services during the investigation phase and how this involvement may affect whether a case is forwarded by police to prosecutors. Police reports (N = 343) of adult sexual assault cases in three midwestern law enforcement agencies were content-analyzed to capture the nature of SANE involvement in the investigation, the specific investigatory steps taken in each case, and the referral outcome. When the victim had a medical forensic exam, police collected more kinds of other evidence to support the case, which was associated with increased likelihood of case referral for prosecution. When SANEs conducted a suspect exam (i.e., a forensic examination of the suspect?s body), police were more likely to collect other kinds of evidence and more likely to interview the suspect, both of which were associated with increased likelihood of case referral.